HUBUNGAN SELF-EFFICACY DAN ADIKSI MEDIA SOSIAL DENGAN PRESTASI AKADEMIK MAHASISWA FAKULTAS AGAMA ISLAM - Moch Haris Anshori; Ika Ratih Sulistiani; Fita Mustafida (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
This study aims to determine the relationship between self-efficacy and social media addiction with student academic achievement. This research was conducted at the Islamic University of Malang, the Faculty of Islamic Studies which began in March until April 2019. The sample in this study was a class of 2015 Islamic Education Study Program students who were randomly selected as many as 90 students. Data obtained from questionnaire data, prerequisite analysis techniques using three prerequisite tests with normality test, linearity test, and multicollinearity test. While the hypothesis testing technique uses multiple regression. The results showed that there was a positive relationship between self-efficacy and social media addiction with the academic achievement of Islamic Religion students, Islamic University of Malang, Islamic Education Study Program, 2015. With calculations (F_count = 22,479 > F_table = 3.10 ) and Column Significance F = 0,000 smaller than the significance of alpha = 0.05.